Two‐Pore K+ Channel TREK‐1 Regulates Sinoatrial Node Membrane Excitability - Sathya D. Unudurthi; Xiangqiong Wu; Lan Qian; Foued Amari; Birce Onal; Ning Li; Michael A. Makara; Sakima A. Smith; Jedidiah Snyder; Vadim V. Fedorov; Vincenzo Coppola; Mark E. Anderson; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundTwo‐pore K+ channels have emerged as potential targets to selectively regulate cardiac cell membrane excitability; however, lack of specific inhibitors and relevant animal models has impeded the effort to understand the role of 2‐pore K+ channels in the heart and their potential as a therapeutic target. The objective of this study was to determine the role of mechanosensitive 2‐pore K+ channel family member TREK‐1 in control of cardiac excitability. Methods and ResultsCardiac‐specific TREK‐1–deficient mice (αMHC‐Kcnkf/f) were generated and found to have a prevalent sinoatrial phenotype characterized by bradycardia with frequent episodes of sinus pause following stress. Action potential measurements from isolated αMHC‐Kcnk2f/f sinoatrial node cells demonstrated decreased background K+ current and abnormal sinoatrial cell membrane excitability. To identify novel pathways for regulating TREK‐1 activity and sinoatrial node excitability, mice expressing a truncated allele of the TREK‐1–associated cytoskeletal protein βIV‐spectrin (qv4J mice) were analyzed and found to display defects in cell electrophysiology as well as loss of normal TREK‐1 membrane localization. Finally, the βIV‐spectrin/TREK‐1 complex was found to be downregulated in the right atrium from a canine model of sinoatrial node dysfunction and in human cardiac disease. ConclusionsThese findings identify a TREK‐1–dependent pathway essential for normal sinoatrial node cell excitability that serves as a potential target for selectively regulating sinoatrial node cell function.